Interest in Using Paylater on the Shopee Application in terms of Convenience, Lifestyle and Risk - Latief, Fitriani; Dirwan, Dirwan; Maulana, Andi Arif (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
The aim of this research is to analyze and test the influence of convenience, lifestyle and risk onInterest in using Paylater on the Shopee application. Quantitative descriptive methods were used in this research, starting with data collection, processing and presenting the results through tables and figures. This research was conducted in the community in Makassar City. The population used in this research is people in Makassar City who use Paylater on the Shopee application. The technique used to determine the sample in this research was purposive sampling technique so that the total sample was 100 people. The data source used in this research is a primary data type data source used obtained from questionnaires distributed to respondents, then the data was processed using the multiple linear regression analysis method. The research results found that there was a significant positive influence from the convenience variable on interest in using Pay later on the Shopee application; there is a significant positive influence of lifestyle variables on interest in using Pay later on the Shopee application; Meanwhile, there is no significant influence of the risk variable on interest in using Pay Later on the Shopee application.